(untitled) (Journal of Engineering, 2023)
Drought is a natural phenomenon in many arid, semi-arid, or wet regions. This showed that no region worldwide is excluded from the occurrence of drought. Extreme droughts were caused by global weather warming and climate change. Therefore, it is essential to review the studies conducted on drought to use the recommendations made by the researchers on drought. The drought was classified into meteorological, agricultural, hydrological, and economic-social. In addition, researchers described the severity of the drought by using various indices which required different input data. The indices used by various researchers were the Joint Deficit Index (JDI), Effective Drought Index (EDI), Streamflow Drought Index (SDI), Standard Precipitation Index (SPI), Standard Evapotranspiration Index (SPEI), and Palmer Index (PI). According to the researchers in hydrology and for the most accurate description of the drought, more than one indicator for drought should be used. Most reviewed studies recommended using the Standard Precipitation Index (SPI) as the best indicator to describe the drought.